Alice Waters: The Chez Panisse Menu Cookbook - Davidson, Alan E (Petits Propos Culinaires, 2025)
Alice Waters: The Chez Panisse Menu Cookbook: Random House, New York, 1982: 312 pp., no illustrations but a captivating photograph of the author on the back of the dust jacket, bibliography, full index, hardback, 16.95.